1990
DOI: 10.1128/mcb.10.9.4816
|View full text |Cite
|
Sign up to set email alerts
|

Enhancers for RNA polymerase I in mouse ribosomal DNA.

Abstract: The intergenic spacer of the mouse ribosomal genes contains repetitive 140-base-pair (bp) elements which we show are enhancers for RNA polymerase I transcription analogous to the 60/81-bp repetitive enhancers (enhancers containing a 60-bp and an 81-bp element) previously characterized from Xenopus laevis. In rodent cell transfection assays, the 140-bp repeats stimulated an adjacent mouse polymerase I promoter when located in cis and competed with it when located in trans. Remarkably, in frog oocyte injection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
104
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 64 publications
1
104
1
Order By: Relevance
“…These include Xenopus and mouse enhancers and ribosomal gene promoter domains from Xenopus, human, rat and mouse (discussed in 12, 37). Nonetheless, UBF from all vertebrate species tested produces essentially identical footprints on various promoter or enhancer probes suggesting that vertebrate UBFs recognize DNA in the same way (7,(12)(13)(14)33). To reconcile these observations it has been suggested that the structure of ribosomal gene promoters may have been conserved in evolution without primary sequence conservation (12).…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…These include Xenopus and mouse enhancers and ribosomal gene promoter domains from Xenopus, human, rat and mouse (discussed in 12, 37). Nonetheless, UBF from all vertebrate species tested produces essentially identical footprints on various promoter or enhancer probes suggesting that vertebrate UBFs recognize DNA in the same way (7,(12)(13)(14)33). To reconcile these observations it has been suggested that the structure of ribosomal gene promoters may have been conserved in evolution without primary sequence conservation (12).…”
mentioning
confidence: 82%
“…Any model that can accommodate a lack of promoter sequence conservation among species that maintain essentially identical transcription factors must invoke the binding of at least one protein with a relaxed specificity for primary sequence. In this regard, UBF is a likely candidate because we have shown that it is clearly a sequence-tolerant protein previously shown to produce discrete footprints on the promoters of all vertebrate species examined (7,(12)(13)(14)33). In addition, UBF can functionally substitute across species boundaries in some cases (13,14), and it is apparently involved in recruiting or stabilizing the TBP-containing activity in transcription complexes on the promoter (10,13,18,33,34,53).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The best characterized thus far is upstream binding factor (UBF). First purified from a human cell fraction required for RNA pol I transcription in vitro (4), UBF was independently purified from Xenopus laevis as an rRNA gene enhancer-binding protein (11,42) and has since been purified and cloned from human, frog, rat, and mouse cells (1,3,17,19,31,34,43,45,57). Immunological evidence suggests that a UBF homolog is also present in protozoa and plants (51).…”
mentioning
confidence: 99%